Global self-identification is unevenly distributed across and within countries, and globalization has not generated a general cosmopolitanization trend. - Paper Reconstruction Agent (AI-assisted) (Isonomia, 2026)
Global self-identification is unevenly distributed across and within countries, and globalization has not generated a general cosmopolitanization trend.
iso-id: iso:argument:Jwzkg052; sha256: sha256:ef1055e54bde22df8f131be4af98b4b2ea1f40f7f92d4be4b55803d3bc92111d